External and public debt crises - Cristina Arellano; Andrew Atkeson; Mark Wright (Federal Reserve Bank of Chicago, 2015)
The recent debt crises in Europe and the U.S. states feature similar sharp increases in spreads on government debt but also show important differences. In Europe, the crisis occurred at high government indebtedness levels and had spillovers to the private sector. In the United States, state government indebtedness was low, and the crisis had no spillovers to the private sector. We show theoretically and empirically that these different debt experiences result from the interplay between differences in the ability of governments to interfere in private external debt contracts and differences in the flexibility of state fiscal institutions.
Keywords: 330; Schuldenkrise; Kreditrisiko; Länderrisiko; Haushaltsdefizit; Finanzpolitik; Kleine offene Volkswirtschaft; Vergleich; USA; Eurozone